The Impact of the World Bank on the Improvements of Consumer Protection in Financial Services and on Developing Financial Literacy in the Czech Republic and Slovakia - Prouza, Tomáš (World Bank, Washington, DC, 2017)
This study analyzes the impact of work of the World Bank in the areas of consumer protection in financial services and in improving financial literacy in the Czech Republic and Slovakia, the first two countries where the World Bank provided technical assistance in the areas of consumer protection in financial services and financial literacy. The impulse of the Czech authorities was their understanding that consumer protection was lacking in the area of financial services while the offer and complexity of financial products was growing rapidly in the quickly developing post-communist market. The authorities were dealing with a growing number of complaints from the public as well as increasing media coverage of consumer complaints, while lacking adequate internal expertise to deal with these issues. The World Bank prepared the technical note on consumer protection in financial services for the Czech Republic. After the note was presented publicly at a dissemination seminar in the Czech Republic, authorities of the Slovak Republic requested similar assistance as they were dealing with similar issues. This study describes the impact the pioneering work of the World Bank team had on the Czech Republic and Slovakia, and how it assisted national authorities in improving consumer protection in financial services and developing programs to increase financial literacy of the Czech and Slovak populations.